MORFOLOGI PERAKARAN TUMBUHAN MONOKOTIL DAN TUMBUHAN DIKOTIL - Dany Roy Putra STG; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2016)
Rooting on the tree is a very important base in growth and development of trees. Not only provide mechanical reinforcement to maintain the structure a tree straight up, but also essential for the absorption of water and minerals. In plants, there are two types of rooting that is tap root on dicots plants and fiber roots in monocots plants. This research can provide information related to the behavior of plant roots on both dicots and monocotyledons and some comparisons root growth between year plant dicots with seasonal and year monocot plants and seasonal. This research was conducted in October 2015 through February 2016 by observe directly in the field. There are twenty species of plants accurate divided into 5 year dicots plants, 5 seasonal dicots plants, 5 year monocot plants and 5 monocot plants seasonal. The results showed the behavior of plant root, root characteristics and a comparison growth of year plant roots and seasonal Keyword : Root, Root Behavior, Monocot, Dicots